Educación Ambiental y actitudes frente a la naturaleza, en los niños/as del quinto grado de Educación General Básica, de la Unidad Educativa “Adolfo Kolping”, en el periodo lectivo 2022-2023 - Espin Villamar, Anahi Lizbeth (2023)
The research project aims to investigate the impact of Environmental Education on the formation of attitudes toward nature in children in the fifth grade of "Adolfo Kolping" Elementary School in the period 2022-2023. Through it, it will be demonstrated that environmental education will change the attitudes, customs, postures, and actions of students to safeguard the nature of the environment where they are. The research was supported by reliable sources, along with the personal contribution of the researcher regarding the problem studied. The population considered was non-probabilistic and was made up of 29 students and a teacher in the fifth grade of elementary school. The methodology used has a mixed approach because there was a relationship between objectivity within the results and subjectivity in observation within the problem posed. Within the qualitative aspect, an interview was applied to the teacher to analyze what her thoughts were related to Environmental Education. At the same time, in the quantitative approach, several techniques and instruments were used that were very helpful for this research, such as the survey with its respective instrument with items and an observation sheet to obtain reliable information and numerical data. The obtained data reflected that the students do not have enough knowledge about environmental care because when classifying the garbage, they do not do it correctly as well as other basic actions that must be carried out conscientiously, and this is where teacher's intervention becomes essential so he can reach it through strategies and recreational activities to generate full awareness and thus maintain a healthy environment.